Selective laser sintering of amorphous nanoparticles: Molecular dynamics simulations - Shtablavyi, I.; Popilovskyi, N.; Nykyruy, Yu.; Mudry, S. (Physics and Chemistry of Solid State, 2024)
The paper investigates the process of liquid-phase sintering of amorphous iron-based nanoparticles by the method of molecular dynamics simulations. The classical molecular dynamics package LAMMPS was used for modeling. Visual analysis of the atomic configurations of nanoparticles during their rapid cooling revealed the self-purification effect of the particles. Partial pair correlation functions and coordination number distribution functions were used to analyze the atomic structure of nanoparticles after sintering. As a result of the analysis of the main structural parameters, which were obtained using the specified functions, differences in the atomic composition and structure of the volume and surface of nanoparticles were established.